2011
DOI: 10.1016/j.jfineco.2011.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Financial literacy and stock market participation

Abstract: Individuals a re increasingly put in charge of their financial security after retirement. Moreover, the supply of complex financial products has increased considerably over the years. However, we still have little or no information about whether individuals have the financial knowledge and skills to navigate this new financial environment. To better understand financial literacy and its relation to financial decision-making, we have devised two special modules for the DNB Household Survey. We have designed que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
427
3
23

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 2,133 publications
(711 citation statements)
references
References 28 publications
38
427
3
23
Order By: Relevance
“…According to their work, these differences are particularly pronounced in rural versus urban areas. This is consistent with the evidence provided in other papers that in the absence of formal education, people acquire financial literacy via interactions with others, for example peers (Duflo andSaez 2003, 2004;Van Rooij et al 2011), and this is more likely in areas with high population density, such as urban areas.…”
Section: The Geography Of Financial Literacysupporting
confidence: 92%
See 1 more Smart Citation
“…According to their work, these differences are particularly pronounced in rural versus urban areas. This is consistent with the evidence provided in other papers that in the absence of formal education, people acquire financial literacy via interactions with others, for example peers (Duflo andSaez 2003, 2004;Van Rooij et al 2011), and this is more likely in areas with high population density, such as urban areas.…”
Section: The Geography Of Financial Literacysupporting
confidence: 92%
“…Financial literacy questions similar to the ones used in the NFCS have been used in Mexico and Chile (Hastings and Tejeda-Ashton 2008;Hastings and Mitchell 2011;Behrman et al 2012), and similar results have been reported in India and Indonesia (Cole et al 2011). The question about bond pricing was first tested in a survey module fielded among Dutch households (Van Rooij et al 2011) and later added to the ALP (Lusardi and Mitchell 2009), and it has been shown to be very effective in differentiating between financially sophisticated and unsophisticated respondents. Across the board, these variables have been found to do a good job of characterizing peoples' levels of financial knowledge.…”
Section: Financial Literacy Questionsmentioning
confidence: 84%
“…We confirm the positive relationship between financial literacy and retirement planning documented, e.g., by Bucher-Koenen and Lusardi (2011), Almenberg andSäve-Söderbergh (2011), andSekita (2011). We also confirm that financially literate households are more likely to participate in financial markets, as shown by Van Rooij et al (2011) for the Netherlands and Yoong (2011) for the United States. We confirm the results of Fornero and Monticone (2011), who find that households with a mortgage display a higher level of financial literacy.…”
Section: Related Literaturesupporting
confidence: 87%
“…First, following up on the studies by Gathergood (2012) and McCarthy (2011) we control for behavioral traits (risk aversion, time preferences) that may be correlated with financial literacy and that may also affect the financial behavior of households and thus their retirement planning. Second, we examine whether the observed correlation between financial literacy and retirement savings carries over to other types of financial behavior, i.e., financial market participation (as in Van Rooij et al 2011) and household borrowing (as in Lusardi and Tufano 2009;Gerardi et al 2010).…”
Section: Robustnessmentioning
confidence: 99%
“…For example, financial literacy has been linked to a number of important outcomes, including wealth accumulation (Stango and Zinman 2009), stock market participation (van Rooij et al 2011;Yoong 2011), and retirement planning (Lusardi and Mitchell 2008). So, the lower levels of financial literacy among women may be impeding their ability to accumulate and manage assets and, ultimately, secure a promising financial future.…”
Section: Introductionmentioning
confidence: 99%